(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Florenskij’s philosophy is atmospheric. I will argue that his aesthetics as a theory of icons is in fact a theory of atmospheres. Therefore, I will show that the late pagan Neoplatonism and the crepuscular phase of medieval Christianity (15th and 16th centuries), which merge within the Slavic Orthodoxy (and Florenskij is imbued with it), come again explicitly in his theory of icons. Finally, I will try and show how Florenskij really reworks this tradition with atmospheric tools ante litteram.